A global approach for the analysis of pecked and polished materials from hunter-gatherer sites - Alvarez Soncini, Maria Celina (2017)
This paper presents the results of the study of materials made by pecking and polishing techniques, belonging to different archeological assemblages from Patagonia and Tierra del Fuego. These kind of tools were not always intentionally made. Sometimes their shapes were produced as a result of formatization and processing of other materials. In any case they could have been part of the production and/or use operating chains of other types of tools.To carry out this study it was necessary to develop a techno-morphological and functional framework. We worked on the basis of experimentation and the application of microscopy techniques, in order to record the manufacturing and utilization traces on the tool?s surfaces. Finally, the analysis of the archaeological materials allowed us to understand the productive processes in which they could have been involved. This approach could allow us to understand the role played by polished and pecked materials in some archaeological hunter-gatherers contexts.